Offene Gemeinwohldefinitionen - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
– Doesn't work. Has failed. Apolitical. Naive. Pre-modern. Non-scientific. Such hardly ornamental epithets get pinned on anybody who still sets out to define the common good today. Ideas and interests cannot be translated into one another without fracture. There is no abstract basic norm from which all normative decisions could be deduced. But neither the individual, nor society and the state can forego a definition of the common good. The ostensive a priori dissolves when a closed definition of the common good is exchanged for an open one. A definition of the common good cannot claim validity once and for all, but always just for one time. Such openness is able to be created with numerous decision-making techniques. The co-existence of incommensurable ideas can be organized through differentiation. Institutions can keep the struggle between conflicting ideas open over the long run. Or decisions and reasons break up. It is easier if the conflict is only settled for the concrete circumstance to be decided upon. Sometimes there is even agreement in the concrete case about the reasons on which a decision is based; more often in any case there is agreement about the decision itself. The plasticity of the definition of the problem can also be used. The need for a decision for which no reasons can be given does not completely disappear with any of these techniques. However, it does diminish. And if it does come to such a decision, that decision is more controlled.
Keywords: 330; Gemeinwohl; Theorie; Öffentliches Interesse